الادارة الجماعية لحقوق المؤلف واصحاب الحقوق المجاورة دراسة تحليلية مقارنة - Karim, Dr. Shang Mohammed Jamil (Journal of Legal and Political Studies, 2025)
This study sheds the light on the legal framework governing Collective management organizations for author rights and the works for related rights, it emphasizes the positive roles these organization plays for both users and right holders, under copyright laws, these organizations operate on behalf of the authors and related rights holders, to protect their rights, manage them as well as distribute The financial returns, since individual management is not possible by authors and in order to encourage both Iraqi and Kurdish legislators to address legislative gaps in their national laws. Keywords:collective management, bodies, copyright, related rights holders
Keywords: Keywordscollective management; bodies; copyright; related rights holders